Reporting on post-menopausal hormone therapy an analysis of gynaecologists' web pages. - Bucksch, Jens (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
The present study was designed to analyse Web pages of German gynaecologists with regard to postmenopausal hormone therapy (HT). There is a growing body of evidence, that the overall health risks of HT exceed the benefits. Making one's own informed choice has become a central concern for menopausal women. The Internet is an important source of health information, but the quality is often dubious. The study focused on the analysis of basic criteria such as last modification date and quality of the HT information content. The results of the Methods: We searched for relevant Web pages by entering a combination of key words (9 x 13 = 117) into the search engine www.google.de. Each Web page was analysed using a standardized questionnaire. The basic criteria and the quality of content on each Web page were separately categorized by two evaluators. Disagreements were resolved by discussion. Main Findings: Of the 97 websites identified, basic criteria were not met by the majority. For example, the modification date was displayed by the only 23 (23.7%) Web pages. The quality of content of most Web pages regarding HT was inaccurate and incomplete. Whilst only nine (9.3%) took up a balanced position, 66 (68%) recommended HT without any restrictions. In 22 cases the recommendation was indistinct and none of the sites refused HT. With regard to basic criteria , there was no difference between HT-recommending Web pages and sites with balanced position. Conclusion: Evidence-based informatino resulting from the WHI trial was insufficiently represented on gynaecologists' Web pages. Because of the growing number of consumers looking online for health information, the danger of obtaining harmful information has to be minimized. Web pages of gynaecologists do not appear to be recommendable for women because they do not provide recent evidence-based findings about HT.